The Impact of Psychological Empowerment on the Development of Creative Thinking: A Field Study of Administrative Employees at King Abdulaziz University in Jeddah - Almahmoudi, Hassan Ahmad (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the impact of psychological empowerment in its four dimensions (meaning, ability, freedom, and influence) on the development of creative thinking among administrative employees at King Abdulaziz University in Jeddah. The study used the descriptive-analytical approach, relying on a questionnaire as a tool that was distributed to a random sample of (381) administrative employees at the university. The results of the study showed a relatively high level of psychological empowerment among administrative employees, as the overall arithmetic mean for the axis reached (3.50). It was found that the dimensions of "meaning" and "ability" were the most prominent and effective, with an arithmetic mean of (3.71), while the participants expressed positions closer to neutrality towards the dimensions of "freedom" with an average of (3.32) and "influence" with an average of (3.24). The results also showed an increase in the level of creative thinking among employees, as the overall arithmetic mean for creative thinking reached (3.42). the study recommended the importance of designing and implementing training and development programs aimed at enhancing the four dimensions of psychological empowerment, with a particular focus on strengthening the dimensions of "freedom" and "influence," by instilling a culture of effective delegation and encouraging participation in the decision-making process.